2003
DOI: 10.1089/153623003321512166
|View full text |Cite
|
Sign up to set email alerts
|

Infection Efficiency of Human and Mouse Embryonic Stem Cells Using Adenoviral and Adeno-Associated Viral Vectors

Abstract: Human and mouse embryonic stem (ES) cells have the capacity to differentiate into derivatives of all three germ layers, suggesting novel therapies for degenerative, metabolic, and traumatic disorders. ES-based regenerative medicine will be further advanced by the development of reliable methods for transgene introduction and expression. Here, we show infection of human and mouse embryonic stem (ES) cells with two of the most popular vectors in gene transfer, adenovirus type 5 (Ad5) and adeno-associated virus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 29 publications
3
64
0
Order By: Relevance
“…Compared with adeno-associated virus vectors, HDAdVs are more efficient in gene delivery into hES cells (20), show a higher ratio of targeted to random integration, and accommodate larger and more complex targeting cassettes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with adeno-associated virus vectors, HDAdVs are more efficient in gene delivery into hES cells (20), show a higher ratio of targeted to random integration, and accommodate larger and more complex targeting cassettes.…”
Section: Discussionmentioning
confidence: 99%
“…Although an E1-deleted AdV was used for gene transfer into hES cells, the transduction efficiency (11%) was low (20). Helper-dependent AdVs (HDAdVs) were originally developed to overcome host immune responses against E1-deleted AdVs in vivo (21,22).…”
mentioning
confidence: 99%
“…Song et al (29) showed repopulation of hepatectomized murine livers with rAAVtransduced oval cells (29), which possess progenitor activity and display CD34 and CD45 surface markers similar to HSC. rAAV transduction of marrow-derived mesenchymal stem cells (30,31), alveolar stem cells (32), neural progenitor cells (33), and embryonic stem cells (34) has been demonstrated. If primitive quiescent HSCs were more efficiently transduced than dividing progenitors, higher marking frequencies in secondary recipients would be expected, as observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these advantageous properties, AAV suffers from several shortcomings, including the inability to target delivery to specific cell types (Muzyczka and Warrington, 2005), inefficient gene delivery to a number of ''nonpermissive'' cell types (Hughes et al, 2002;Ponnazhagan et al, 1996;Smith-Arica et al, 2003;Stacchini et al, 1999), a limited packaging insert size (Dong et al, 1996), and the prevalence of pre-existing immunity to human AAV serotypes in the human population (Moskalenko et al, 2000;Sun et al, 2003).…”
Section: Adeno-associated Virusmentioning
confidence: 99%